2015
DOI: 10.1186/s12936-015-0727-y
|View full text |Cite
|
Sign up to set email alerts
|

Coverage, use and maintenance of bed nets and related influence factors in Kachin Special Region II, northeastern Myanmar

Abstract: BackgroundMyanmar is one of the 31 highest burden malaria countries worldwide. Scaling up the appropriate use of insecticide-treated nets (ITNs) is a national policy for malaria prevention and control. However, the data on use, influencing factors and maintenance of bed nets is still lack among the population in Kachin Special Region II (KR2), Northeastern Myanmar.MethodsThe study combined a quantitative household questionnaire survey and qualitative direct observation of households. A Chi-squared test was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 30 publications
8
67
5
Order By: Relevance
“…Furthermore, although people may reside inside houses during night time, they could not reasonably be expected to be under a net since household activities such as cooking need to be conducted. The bednet policy in Malaysia is to annually treat nets owned by households, replenish damaged nets and distribute LLINs so that households have a maximum of two people per net (21). Given the changing malaria situation in the country, continued efforts are needed to emphasise the bene ts of operational vector control activities for eliminating any localized residual foci of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although people may reside inside houses during night time, they could not reasonably be expected to be under a net since household activities such as cooking need to be conducted. The bednet policy in Malaysia is to annually treat nets owned by households, replenish damaged nets and distribute LLINs so that households have a maximum of two people per net (21). Given the changing malaria situation in the country, continued efforts are needed to emphasise the bene ts of operational vector control activities for eliminating any localized residual foci of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The Ministry of Health, Myanmar began distributing ITNs to families in rural endemic areas to prevent vectorborne disease such as Malaria, dengue fever, JE, etc. [14]. Free distribution of ITNs resulted in a higher rate of ownership among the poor.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of ITNs is related to many factors. A study of the use and maintenance of bed nets and related influencing factors in Kachin Special Region in 2015 revealed that residents consist of poor families, living under thatched roofing, with limited knowledge of how to prevent disease transmission [14]. The Ministry of Health, Myanmar began distributing ITNs to families in rural endemic areas to prevent vectorborne disease such as Malaria, dengue fever, JE, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some models do allow for hosts who only intermittently apply personal protection (such as hosts who sleep under bed nets only at night), but even in these cases, assignments to sporadically protected and completely unprotected classes typically remain fixed [28,29]. In reality, protection status is dynamic: people forget to apply repellent, run out of repellent, wear down their bed nets, or grow weary of protection efforts and thus falter in compliance [30,31], and non-compliant individuals can potentially re-acquire protection or re-adopt its use. This is particularly true if rigorous campaign initiatives are mounted in support of personal protection use.…”
Section: Introductionmentioning
confidence: 99%